Preparation method and application of porous ceramic material with high through hole rate
By using lead, zinc ore waste slag and other raw materials to prepare porous ceramic materials with high through-porosity, the problems of high cost of production raw materials and poor through-porosity in the prior art are solved, and the effects of cost reduction and performance improvement are achieved.
Patent Information
- Application Number
- CN202411384169.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
There are problems such as high cost of production raw materials and poor throughput during the preparation of existing porous ceramic materials and their ceramic filter membranes.
High-through porous ceramic materials are prepared by using raw materials such as lead-zinc ore waste residue, skeleton materials, pore-making agents and plasticizers through stirring and mixing, vacuum slurry, staleness, forming and firing.
The through-porosity and flexural strength of porous ceramic materials are improved, the production cost of ceramic membranes is reduced, and the social benefits of green, low-carbon and environmental protection are achieved.
Smart Images

Figure CN119390474A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous ceramic materials, and in particular relates to a preparation method and application of a porous ceramic material with high through-porosity. Background Art
[0002] Porous ceramics are a new type of ceramic material with uniformly distributed micropores or holes, high porosity and low volume density. At the same time, porous ceramics have a developed specific surface area and unique physical surface properties, and are selectively permeable to liquid and gas media. Porous ceramics also have energy absorption or damping properties. In addition, ceramic materials have unique high temperature resistance, corrosion resistance, high chemical stability and dimensional stability. This makes porous ceramics, a green material, widely used in gas or liquid filtration, purification and separation, chemical catalytic carriers, sound absorption and shock absorption, advanced thermal insulation materials, biological implant materials, special wall materials and sensor materials.
[0003] Porous ceramic materials can be divided into two categories according to the state of the internal pores: closed pores that are independent of each other and open pores that are interconnected. The preparation of pores in closed pore ceramics can be roughly divided into two categories: high-temperature preparation and low-temperature preparation. The high-temperature preparation is obtained by using the pore-forming agent to produce gas after the viscous liquid phase such as glass appears inside the ceramic at high temperature. The low-temperature preparation is to use a foaming agent to produce a large number of bubbles in the ceramic slurry, and then seal the bubbles in the ceramic body, and then sinter it to obtain porous ceramics with mainly closed pores. The preparation of open pore ceramics is generally obtained by forming interconnected gas phase gaps between the solid phase particles of the ceramic after high-temperature sintering. In order to obtain a high porosity, it is usually necessary to use a pore-forming agent. However, in the current preparation process of open pore ceramics, there are problems such as high production raw material costs and poor porosity. Summary of the invention
[0004] In view of the above-mentioned deficiencies, the present invention discloses a method for preparing a porous ceramic material with high through-porosity and its application, which solves the problems of high raw material cost and poor through-porosity of porous ceramics in the preparation process of existing porous ceramic materials and ceramic filter membranes.
[0005] The present invention is achieved by adopting the following technical solutions: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weigh the following raw material components in weight percentage: 40-80% lead-zinc ore waste, 10-50% framework material, 10-35% pore former, and 0-12% plasticizer; the lead-zinc ore waste includes the following components in weight percentage: 30-60% silicon oxide, 4-28% aluminum oxide, 6-20% iron oxide, 5-20% calcium oxide, 0.5-6% magnesium oxide, 0-6% sulfur trioxide, and 2-7% other oxides; the framework material is one or more combinations of aluminum oxide, silicon oxide, clay, kaolin, high aluminum product waste, bauxite, and zircon sand, and a suitable framework material is selected in combination with the lead-zinc ore waste, so that the prepared porous ceramic material has the ability to maintain a certain shape at high temperature and can improve the strength of the porous ceramic material; (2) The lead-zinc mine waste slag, skeleton material, pore-forming agent and / or plasticizer are stirred and mixed evenly, and then water is added and stirred continuously to obtain a plastic green body; the green body is subjected to vacuum mud kneading and then aged for 48 hours, and then the green body is formed and dried, and then placed in a kiln for firing to obtain a high-porosity porous ceramic material, wherein the highest firing temperature during the firing process is 1000-1300°C.
[0006] The other oxides include potassium oxide, sodium oxide, manganese oxide, titanium oxide, zinc oxide and the like.
[0007] Furthermore, in step (1), the pore-forming agent is one or more combinations of starch, rice husk powder, cellulose, and graphite powder. According to the characteristics of the lead-zinc ore waste, by screening and adding a suitable pore-forming agent, during firing, the pore-forming agent is burned away, leaving pores in the ceramic body, thereby playing a role in improving the through-porosity.
[0008] Furthermore, in step (1), the plasticizer includes one or more combinations of methyl cellulose, ethyl cellulose, PVA, HPMC, and tung oil. By selecting and supplementing suitable plasticizers, the plasticity of the blank can be improved when plastic forming (such as extrusion forming) is used.
[0009] Furthermore, in step (1), the following raw material components are weighed in weight percentage: 60-75% of lead-zinc ore waste, 15-40% of skeleton material, 10-25% of pore-forming agent, and 0-7% of plasticizer; the skeleton material is a combination of aluminum oxide, silicon oxide and clay, the pore-forming agent is starch, and the plasticizer is HPMC.
[0010] Furthermore, in step (2), the lead-zinc ore waste slag is first crushed and put into a ball mill or a Raymond mill to grind into lead-zinc ore waste slag fine powder, and then stirred and mixed with the skeleton material, pore-forming agent and / or plasticizer to be uniformly mixed, and the particle size of the lead-zinc ore waste slag fine powder is not higher than 150 microns.
[0011] Furthermore, in step (2), during the sintering process, the holding time at the highest sintering temperature is 2 to 3 hours.
[0012] Furthermore, in step (2), the forming method is any one of plastic forming, grouting forming, pressing forming, injection molding and hot pressing forming. The injection molding method can adopt an acrylamide series injection molding system, a carrageenan injection molding system, an agarose injection molding system, etc. The blank preparation process is determined according to the forming method. For plastic forming, mixing, vacuum mud kneading, aging and other processes are used to prepare blanks with good plasticity; for grouting forming and injection molding, a wet ball milling process is used to prepare mud with high solid content and good fluidity; for dry pressing forming, a powdering or spray drying process is used to prepare granular powder with good fluidity and high filling density; for hot pressing forming, a mixing process is used to mix the blank with paraffin to prepare a wax cake.
[0013] Furthermore, in step (2), the drying temperature is 50-80° C., and the moisture content of the blank after drying is less than 3%.
[0014] Furthermore, the high-through-porosity porous ceramic material obtained in step (2) has a flexural strength greater than 45 MPa, an apparent porosity greater than 45%, and an average pore size of 0.6 to 10 μm.
[0015] The porous ceramic material with high porosity is used to prepare ceramic filtration membranes.
[0016] Compared with the prior art, this technical solution has the following beneficial effects: 1. In the preparation process of open pore ceramics, i.e. porous ceramics with high through-porosity, the main processes that affect its through-porosity are blank composition, preparation process and product firing. The composition of the blank and its preparation technology determine the size of the pore size and the level of through-porosity, and low-quality lead-zinc mine waste slag cannot obtain a suitable pore size and through-porosity when used as a raw material for preparing ceramics. The present invention crushes the lead-zinc mine waste slag to a certain particle size and screens it before mixing it with raw materials such as skeleton materials, pore formers, plasticizers, etc., so that various effective ingredients in the lead-zinc mine waste slag can be fully utilized, such as aluminum, silicon and other high-refractory aggregate components, as well as low-temperature fusible components, so that the lead-zinc mine waste slag can not only have a certain skeleton effect, but also play the role of a binder, which is beneficial to improving the flexural strength of the ceramic.
[0017] 2. One of the application products of high-porosity porous ceramic materials is ceramic filter membrane. At present, ceramic filter membranes are mainly prepared from chemical materials such as aluminum oxide, zirconium oxide, titanium oxide, and silicon carbide. The high price of raw materials leads to high production costs of ceramic membranes, which has an adverse effect on the promotion of the application market of ceramic membranes. The present invention uses a large amount of lead-zinc mine waste slag as raw material to prepare high-porosity porous ceramic materials, which can simultaneously improve the porosity and strength of porous ceramics. The material is used to manufacture ceramic membrane products, which can greatly reduce the production cost of ceramic membranes (the cost of ceramic blanks can be reduced by 60% to 90% compared with aluminum oxide blanks, and the production energy consumption cost can be reduced by more than 15%). At the same time, through the waste utilization of slag, the social benefits of green, low-carbon and environmental protection can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a 10 μm electron microscope image of the flat ceramic membrane plate obtained in Example 1.
[0019] Figure 2 This is a 2 μm electron microscope image of the flat ceramic membrane plate obtained in Example 1.
[0020] Figure 3 This is the pore size distribution diagram of the flat ceramic membrane plate obtained in Example 1.
[0021] Figure 4 This is a product photo of the flat ceramic diaphragm plate obtained in Example 1. DETAILED DESCRIPTION
[0022] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0023] Embodiment 1: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weigh the following raw material components: 7 kg lead-zinc ore waste, 1.0 kg alumina powder, 1.3 kg silicon oxide, 0.7 kg kaolin, 1.6 kg starch, 0.5 kg HPMC, 350 g tung oil, and 2.5 kg water; the lead-zinc ore waste includes the following components in percentage by weight: 43.05% silicon oxide, 11.47% aluminum oxide, 16.88% ferric oxide, 15.53% calcium oxide, 4.52% magnesium oxide, 4.24% sulfur trioxide, and 4.31% other oxides, including potassium oxide, sodium oxide, manganese oxide, titanium oxide, and zinc oxide; (2) First, the lead-zinc ore waste slag is crushed and put into a ball mill to grind into lead-zinc ore waste slag fine powder, and then mixed with the remaining raw materials except water, wherein the particle size of the lead-zinc ore waste slag fine powder is 100 microns, and then water is added and stirred to obtain a plastic blank; the blank is vacuum-kneaded and aged for 48 hours, and then the blank is extruded into a shape to obtain a flat ceramic membrane plate, which is then dried at a drying temperature of 65°C. The moisture content of the dried flat ceramic membrane plate is 2.5%, and then placed in a kiln to obtain a flat ceramic membrane plate. During the firing process, the plate is kept warm at a maximum firing temperature of 1200°C for 2 hours; the flat ceramic membrane plate has a flexural strength of 45MPa, an apparent porosity of 46%, an average pore size of 1.05 microns, and an air flux of 4500 M 3 / M 2 ·h·ba.
[0024] The two ends of the obtained flat ceramic membrane are sealed, one end is completely closed, and the other end is closed with a through-hole interface to connect to the outside, thereby making a ceramic filter membrane element. The through-hole interface at one end of the ceramic membrane filter element is connected to a pump, and then the ceramic membrane filter element is placed in turbid sewage, and the pump is started. The water extracted after filtration by the ceramic membrane becomes clear and clean. It can effectively filter sewage and can be used in environmental protection fields such as water treatment.
[0025] Embodiment 2: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weigh the following raw material components: 4 kg lead-zinc ore waste residue, 4.3 kg high-aluminum product waste powder, 0.5 kg silicon oxide, 1.2 kg kaolin, 1.35 kg starch and rice husk powder in total, 0.5 kg methyl cellulose, and 1.8 kg PVA aqueous solution; the lead-zinc ore waste residue includes the following components in weight percentage: 30.56% silicon oxide, 28.64% aluminum oxide, 10.25% iron oxide, 18.69% calcium oxide, 0.65% magnesium oxide, 5.98% sulfur trioxide, and 5.23% other oxides, including potassium oxide, sodium oxide, manganese oxide, titanium oxide, and zinc oxide; (2) Firstly, the lead-zinc ore waste slag is crushed into a Raymond mill to be ground into a lead-zinc ore waste slag fine powder, and then the lead-zinc ore waste slag fine powder is mixed evenly with the remaining raw materials except the PVA aqueous solution, wherein the particle size of the lead-zinc ore waste slag fine powder is 100 microns, and then the PVA aqueous solution is added and continued to be stirred evenly, and then pressed into a block, and then the block blank is processed into powder by a powder grinder, and the blank powder is passed through a 30-mesh sieve to obtain a blank powder; the blank powder is pressed into shape on a press to obtain a ceramic membrane blank, and then the ceramic membrane blank is dried at a drying temperature of 50°C. The moisture content of the dried blank is 2.5%, and then it is placed in a kiln to be fired to obtain a ceramic membrane plate. During the firing process, the ceramic membrane plate is kept warm at a maximum firing temperature of 1250°C for 2 hours; the flexural strength of the ceramic membrane plate is 73MPa, the apparent porosity is 60%, the average pore size is 6.9 microns, and the air flux is 6200 M 3 / M 2 ·h·ba.
[0026] Embodiment 3: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weigh the following raw material components: 6 kg lead-zinc ore waste, 1.6 kg bauxite powder, 0.3 kg silicon oxide, 2.1 kg kaolin, 1.8 kg graphite powder, 0.15 kg ethyl cellulose, and 3.9 kg water; the lead-zinc ore waste includes the following components in percentage by weight: 59.47% silicon oxide, 4.78% aluminum oxide, 6.88% iron oxide, 15.26% calcium oxide, 5.77% magnesium oxide, 1.02% sulfur trioxide, and 6.82% other oxides, including potassium oxide, sodium oxide, manganese oxide, titanium oxide, and zinc oxide; (2) First, the lead-zinc mine waste slag is crushed and mixed with the remaining raw materials, and then the mixture is evenly mixed in a ball mill and ground for 6 hours. The material is then sieved through a 100-mesh sieve to obtain a slurry of ceramic membrane blank; the slurry is cast on a gypsum mold, and after drying and demolding, a single-hole ceramic membrane tube blank is obtained, and then the single-hole ceramic membrane tube blank is dried at a drying temperature of 70°C. The moisture content of the dried blank is 2%, and then the blank is placed in a kiln for firing to obtain a single-hole ceramic membrane tube. During the firing process, the blank is kept warm at a maximum firing temperature of 1180°C for 2.5 hours; the single-hole ceramic membrane tube has a flexural strength of 50 MPa, an apparent porosity of 49%, an average pore size of 0.6 microns, and an air flux of 3300 M 3 / M 2 ·h·ba.
[0027] Embodiment 4: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weigh the following raw material components: 8 kg lead-zinc ore waste, 1.6 kg alumina powder, 0.4 kg kaolin, 1.1 kg starch, and 3.5 kg water; the lead-zinc ore waste includes the following components in weight percentage: 45.32% silicon oxide, 12.47% aluminum oxide, 15.24% iron oxide, 16.33% calcium oxide, 4.05% magnesium oxide, 4.18% sulfur trioxide, and 2.41% other oxides; (2) The lead-zinc mine waste residue is crushed and mixed with the remaining raw materials, and then put into a ball mill and grind for 12 hours. The material is then sieved through a 180-mesh sieve to obtain a slurry of ceramic membrane blanks, and the slurry is heated to 80°C for use; 0.33 kg of agarose is weighed and put into 2 kg of water, and heated to 90°C to obtain an agarose solution for use; the 90°C agarose solution is poured into the 80°C slurry, stirred evenly, and poured into a mold, and after the blank in the mold is cooled and solidified, it is demolded to obtain a ceramic membrane blank; the ceramic membrane blank is dried at a drying temperature of 80°C, and the moisture content of the dried blank is 2%, and then placed in a kiln to obtain a ceramic membrane. During the firing process, the blank is kept warm at a maximum firing temperature of 1130°C for 3 hours; the flexural strength of the ceramic membrane is 45 MPa, the apparent porosity is 58%, the average pore size is 3.9 microns, and the air flux is 5000 M 3 / M 2 ·h·ba.
[0028] Embodiment 5: A method for preparing a porous ceramic material with high through-porosity, comprising the following steps: (1) Weighing 1.5 kg of lead-zinc ore waste slag, subjecting it to ball milling and sieving to obtain lead-zinc ore waste slag powder, then mixing the lead-zinc ore waste slag powder with 50 g of acrylamide, 12 g of N,N-methylenebisacrylamide, 35 g of water reducer sodium polyacrylate, and 560 g of water, adding the mixture to a ball mill for 2 hours, and then discharging the mixture through a 180-mesh sieve to obtain a slurry for standby use; the lead-zinc ore waste slag comprises the following components in weight percentage: 43.05% silicon oxide, 11.47% aluminum oxide, 16.88% iron oxide, 15.53% calcium oxide, 4.52% magnesium oxide, 4.24% sulfur trioxide, and 4.31% other oxides, wherein the other oxides include potassium oxide, sodium oxide, manganese oxide, titanium oxide, and zinc oxide; (2) Weigh 7 g of initiator (ammonium persulfate, potassium persulfate or sodium persulfate) and 3 g of catalyst, add them to 50 g of water, stir and dissolve to obtain an initiator solution; (3) adding the initiator solution in step (2) to the slurry obtained in step (1), stirring evenly and pouring into a plastic mold, and after the slurry in the mold solidifies, drying and demolding to obtain a green body of the ceramic membrane; (4) The green body obtained in step (3) is placed in a drying chamber and dried at 60°C, and then the dried ceramic membrane is placed in a kiln for firing. During the firing process, the ceramic membrane is kept at a maximum firing temperature of 1100°C for 2 hours, and then cooled to obtain a ceramic membrane. The ceramic membrane has a flexural strength of 100 MPa, an apparent porosity of 46%, an average pore size of 0.5 to 0.6 microns, and an air flux of 200 M 3 / M 2 ·h·ba.
[0029] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a porous ceramic material with high through-porosity, characterized in that: The following steps are involved: (1) Weigh the following raw material components in weight percentage: 40-80% lead-zinc ore waste, 10-50% framework material, 10-35% pore former, and 0-12% plasticizer; the lead-zinc ore waste includes the following components in weight percentage: 30-60% silicon oxide, 4-28% aluminum oxide, 6-20% iron oxide, 5-20% calcium oxide, 0.5-6% magnesium oxide, 0-6% sulfur trioxide, and 2-7% other oxides; the framework material is one or more combinations of aluminum oxide, silicon oxide, clay, kaolin, high aluminum product waste, bauxite, and zircon sand; (2) The lead-zinc mine waste slag, skeleton material, pore-forming agent and / or plasticizer are stirred and mixed evenly, and then water is added and stirred continuously to obtain a plastic green body; the green body is subjected to vacuum mud kneading and then aged for 48 hours, and then the green body is formed and dried, and then placed in a kiln for firing to obtain a high-porosity porous ceramic material, wherein the highest firing temperature during the firing process is 1000-1300°C.
2. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (1), the pore-forming agent is one or more combinations of starch, rice husk powder, cellulose, and graphite powder.
3. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (1), the plasticizer includes one or more combinations of methyl cellulose, ethyl cellulose, PVA, HPMC, and tung oil.
4. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (1), the following raw material components are weighed in weight percentage: 60-75% of lead-zinc ore waste, 15-40% of skeleton material, 10-25% of pore-forming agent, and 0-7% of plasticizer; the skeleton material is a combination of aluminum oxide, silicon oxide and clay, the pore-forming agent is starch, and the plasticizer is HPMC.
5. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (2), the lead-zinc ore waste slag is first crushed and put into a ball mill or a Raymond mill to grind into lead-zinc ore waste slag fine powder, and then stirred and mixed with the skeleton material, pore-forming agent and / or plasticizer to be uniform, and the particle size of the lead-zinc ore waste slag fine powder is not higher than 150 microns.
6. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (2), during the sintering process, the holding time at the highest sintering temperature is 2 to 3 hours.
7. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (2), the forming method is any one of plastic forming, slip casting, compression forming, gel casting and hot compression molding.
8. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: In step (2), the drying temperature is 50-80° C., and the moisture content of the blank after drying is less than 3%.
9. The method for preparing a porous ceramic material with high through-porosity according to claim 1, characterized in that: The high-through-porosity porous ceramic material obtained in step (2) has a flexural strength greater than 45 MPa, an apparent porosity greater than 45%, and an average pore size of 0.6 to 10 μm.
10. Use of the porous ceramic material with high through-porosity as claimed in claims 1 to 10, characterized in that: The porous ceramic material with high porosity is used to prepare a ceramic filter membrane.
Citation Information
Patent Citations
Method for producing ceramic insulation board by tailings of lead zinc ore
CN103739274A
Method for preparing environment-friendly honeycomb ceramic heat accumulator by use of waste slag
CN103992099A
Method for preparing environment-friendly ceramic vitrified brick by using waste slag
CN104003700A
Lead-zinc tailing-red mud-flyash-based foamed ceramic and preparation method thereof
CN104529518A
Method of using lead-zinc tailings as raw materials for preparing water-permeable glass bricks through hot-press sintering approach
CN109942198A